Manifesting the Sacred: John La Farge’s The Lampbearer as a Model for Catholic Presence in the World - LaBadie, Benjamin (Lumen et Vita, 2015)
What does it mean for the Church to be in the world? In this paper, I propose that it means for the Church to be sacred, i.e., all Catholics are called to live sacredly. How is the sacred defined? To answer this question, I look to the American artist, John La Farge (1835-1910), whose works are currently being displayed at Boston College's McMullen Museum. The exhibition examines La Farge's "lifelong efforts to visualize the sacred." Given this, I offer a theological reflection on La Farge's painting of the Wise Virgin in order to elucidate what it means to live sacredly: being in tension between the transcendent and the imminent. In other words, to live sacredly means to be attentive, patient, and faithful to the ultimate coming of God's kingdom, yet also to be present, patient, and concerned with the practical worldly challenges of today. This sacredness begins to manifest God's love and kingdom on Earth even if there is still a longing for God’s full glory which is not yet present. This is how the Church is to be in the world. The Church should be attentive to the numerous challenges on Earth while remembering her ultimate end is union with God in Heaven. To forget this latter point would make the Church a mere NGO detached from God while to forget the former would make the Church an arthritic institution detached from those who suffer. Therefore, all Catholics are called to live in the tension between the transcendent and the imminent.